A rare diagnosis: Acute bilateral vasitis mimicking incarcerated bilateral inguinal hernia - Bassam Hussain Mohammed Bugis; Mishal Alarifi; Saeed Alzahrani; Rami Hasan (Urology Annals, 2023)
Inflammation of the vas deferens or what known as acute vasitis is an under-reported condition that usually presents with scrotal or inguinal pain and swelling which can be misdiagnosed and treated as many other conditions. Here, we present one of the first cases to be reported in the literature with bilateral manifestation. A 28-year-old male patient presented complaining of bilateral testicular and inguinal pain associated with inguinal swelling for 3 days. Initially, the patient was being evaluated as a case of incarcerated bilateral inguinal hernia, but with the aid of radiological imaging, the patient was diagnosed correctly and the unnecessary surgical intervention was prevented.